Review of the minibasket rules in the differents regions of Spain - Celestina Vizcaíno Domínguez; Pedro Sáenz- López Buñuel; José Antonio Rebollo González (Federación Extremeña de Balonmano; University of Extremadura, 2013)
The adaptation of the rules of basketball at the age and abilities of children that start through  minibasket has been very positive for the sport initiation to the sport. However, in Spain, these rules have been developed in different ways in each region. This fact has its positives and negatives. We analyze all the different regulations governing minibasket competitions in order to check the rules more frequent and educative, and make proposals for improvement to minibasket rules. Some regions such as Andalusia, Catalonia and Galicia develop more specific and comprehensive rules. The rules of time and space are the most repeated in the various regulations. It is suggested to unify the rules and emphasize the most important for the game and for the training of players. Key words: